2010
DOI: 10.4064/dm473-0-1
|View full text |Cite
|
Sign up to set email alerts
|

Algebra in the superextensions of twinic groups

Abstract: Given a semilattice X we study the algebraic properties of the semigroup υ(X) of upfamilies on X.The semigroup υ(X) contains the Stone-Čech extension β(X), the superextension λ(X), and the space of filters ϕ(X) on X as closed subsemigroups. We prove that υ(X) is a semilattice iff λ(X) is a semilattice iff ϕ(X) is a semilattice iff the semilattice X is finite and linearly ordered. We prove that the semigroup β(X) is a band if and only if X has no infinite antichains, and the semigroup λ(X) is commutative if and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…Moreover Q 2 ∞ is locally nilpotent but not nilpotent, and every element of Q 2 ∞ \C 2 ∞ has order 4. Let C t denote the cyclic group of order t ∈ N. It is well known that a 2-group has an unique element of order 2 if and only if it is isomorphic to C 2 n or Q 2 n for some n ∈ N ∪ {∞} (see, for instance, [1,Theorem 8.1]). It easily follows that the infinite quaternion group is anticommutative.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Moreover Q 2 ∞ is locally nilpotent but not nilpotent, and every element of Q 2 ∞ \C 2 ∞ has order 4. Let C t denote the cyclic group of order t ∈ N. It is well known that a 2-group has an unique element of order 2 if and only if it is isomorphic to C 2 n or Q 2 n for some n ∈ N ∪ {∞} (see, for instance, [1,Theorem 8.1]). It easily follows that the infinite quaternion group is anticommutative.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Difference bases and difference characteristics in dihedral and Abelian groups were investigated in [3,4]. Difference bases have applications in the study of structure of superextensions of groups, see [1,5,9].…”
Section: Theorem 4 ([13]mentioning
confidence: 99%
“…The superextensions of semilattices were studied in [4]. In particular, it was shown that λ(L 3 ) ∼ = L 4 , and hence Aut (λ(L 3 )) ∼ = Aut (L 4 ) ∼ = C 1 .…”
Section: Proposition 6 Let Z Be the Zero Of The Null Semigroupmentioning
confidence: 99%